The antecedents and consequences of turnover intention during pandemic until post covid-19 pandemic: Systematic literature review - Elfira Nadya Anggraini; Rizki Sridadi (Institute of Computer Science (IOCS), 2023)
Turnover intention has become a managerial issue for academics and practitioners concern in human resource management science, which is the most important cause of turnover behavior. This study attempts to examine the potential consequences of turnover intention and contributes to the literature on turnover intention from the impact of antecedents and consequences on the research analysis unit during 2020 until 2023. This research used the Systematic Literature Review (SLR) method, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. From the screening of 138 articles collected from the Scopus database, that fulfill the requirements found 225 antecedents and 7 consequences of turnover intention. The results show that antecedents and consequences are found in the scope of turnover intention from research analysis unit in public and private sector. From the 225 antecedents then analyzed into the following 9 categories: Work Attitudes, Job Strains, HRM Practices, Interrole Conflicts, Supervisor/Leader Behaviors, Emotional Labor, Employee Performance, Organizational Contextual Factors, and Individual Attributes. Meanwhile, the 7 consequences found were: Dysfunctional Audit Behavior, Organizational Commitment, Psychological Contract Breach, Quality of Service Performance, Social Loafing Behavior, Voluntary Turnover, and Work Deviance Behavior.